Persistence of divergent views of hospital staff in detecting and managing hypertension. Issue 6456 (24th November 1984) - Manek, S; Rutherford, J; Jackson, S H; Turner, P
Abstract : A questionnaire concerning views of hospital clinical staff was completed by 408 out of 542 staff (75%), comprising 214 medical staff of all clinical specialties, 106 first year clinical medical students, and 88 third year student nurses. On average 386 of 407 (95%) thought that blood pressure should be measured routinely in all inpatients but only 294 of 404 (73%) thought that this was appropriate for outpatients. Although 251 of 390 (64%) were taught to use the muffling of sounds (phase IV) as the diastolic blood pressure, only 219 of 406 (54%) actually used this phase alone. There were appreciable differences between the grades of staff in this respect, a small majority of most grades using phase IV. Roughly half (50 out of 102) of the medical student respondents were taught to use phase IV, but only 38 of 106 (36%) were actually using this phase. While only three out of 16 general practitioners were using phase IV diastolic blood pressure alone, the figure was 66 out of 88 (75%) for student nurses. The level of diastolic blood pressure at which clinicians would begin to treat a 50 year old asymptomatic man ranged from 90 to 121 mm Hg. When these figures were corrected to phase V values, assuming a 5 mm Hg difference between phases IV and V, the range was 85 to 116 mm Hg. Despite the general agreement among physicians interested in hypertension that the disappearance of sounds (phase V) should be used to denote diastolic blood pressure there is still considerable divergence of opinion among hospital medical staff.